INFLUENCE OF THE PLACEBO EFFECT ON THE RECOVERY OF PATIENTS WITH CARPAL TUNNEL SYNDROME - Aycha Zaralieva; Mariela Filipova (Peytchinski Publishing, 2022)
The placebo effect is a phenomenon of influencing certain clinical symptoms under the influence of drugs or medical manipulations that completely resemble the real ones. An increasing number of clinical trials on the effects of oral, parenteral and topical medications, as well as hardware procedures, are being conducted with placebo control groups to clarify the real clinical effect of the substances or methods used. Methods: A total of 30 patients with carpal tunnel syndrome were investigated. In our study, we compared the effect of actually applied low-frequency pulsed magnetic field treatment and Ultraphonophoresis with Contractubex in the carpal tunnel area with а placebo. Patients were informed in advance that some of them would fall into the placebo group but would not know which ones. Results and analysis: The result of the registration of the persons intended during the treatment in both groups and in the follow-up examination show that the pain is weaker at the end of the treatment course. Conclusion: The use of preformed factors gives better results in reducing the pain syndrome within the treatment course, but it is not more effective in the long run than using a placebo.